Tissue factor over-expression in platelets of patients with anti-phospholipid syndrome: induction role of anti-β2-GPI antibodies. (15th January 2019) - Capozzi, A; Manganelli, V; Riitano, G; Recalchi, S; Truglia, S; Alessandri, C; Longo, A; Garofalo, T; Misasi, R; Valesini, G; Conti, F; Sorice, M
Summary: Anti-phospholipid syndrome (APS) is characterized by arterial and/or venous thrombosis and pregnancy morbidity. It is well known that in these patients thrombosis may be the result of a hypercoagulable state related to anti-β2-glycoprotein I (β2-GPI) antibodies. Moreover, platelets may play a role in thrombotic manifestations by binding of anti-β2-GPI antibodies. Platelets express tissue factor (TF), the major initiator of the clotting cascade, after activation. We primarily analyzed whether anti-β2-GPI antibodies may trigger a signal transduction pathway leading to TF expression in human platelets. Platelets from healthy donors were incubated with affinity purified anti-β2-GPI antibodies for different times. Platelet lysates were analyzed for phospho-interleukin-1 receptor-associated kinase 1 (IRAK), phospho-p65 nuclear factor kappaB (NF-κB) and TF by Western blot. IRAK phosphorylation was observed as early as 10 min of anti-β2-GPI treatment, with consequent NF-κB activation, whereas TF expression, detectable at 45 min, was significantly increased after 4 h of anti-β2-GPI treatment. Virtually no activation was observed following treatment with control immunoglobulin IgG. We then analyzed TF expression in platelets from 20 APS patients and 20 healthy donors. We observed a significant increase of TF in APS patients versus control subjects ( P < 0·0001). This work demonstrates that anti-β2-GPI antibodies may trigger in vitro a signal transduction pathway in human platelets, which involves IRAK phosphorylation and NF-κB activation, followed by TF expression. Furthermore, ex vivo, platelets of APS patients showed a significantly increased expression of TF. These findings support the view that platelets may play a role in the pathogenesis of APS, with consequent release of different procoagulant mediators, including TF. Graphical Abstract: